2015
DOI: 10.17957/ijab/14.0003
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Evaluation of Fresh and Wilted Mixed Silage of Naked Oats (Avena nuda) and Alfalfa (Medicago sativa)

Abstract: To cite this paper: Jian, G., Y. Cuijun and L. Guihe, 2015. Analysis to wilting and mixed silage effect on naked oats(Avena nuda) and alfalfa (Medicago sativa AbstractNutritional evaluation of fresh and wilted silage made of Naked Oats (Avena nuda L.) and Alfalfa (Medicago sativa L.) in different proportions (0:1, 1:0, 1:1, 2:1 and 1:2) was carried out in present study. The changes between fermentation quality and nutrition composition were observed after 60 days. The results based on sensory evaluation show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 3 publications
2
11
0
Order By: Relevance
“…In addition, CP content was higher in mixed silage with increased CF ratio, because the CP of CF material is high. This is consistent with the previous reports on Napier grass-phasey bean silage, Chinese wildrye-alfalfa silage and naked oats-alfalfa silage (Ge et al, 2015;Pan et al, 2014;Yunus et al, 2001).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, CP content was higher in mixed silage with increased CF ratio, because the CP of CF material is high. This is consistent with the previous reports on Napier grass-phasey bean silage, Chinese wildrye-alfalfa silage and naked oats-alfalfa silage (Ge et al, 2015;Pan et al, 2014;Yunus et al, 2001).…”
Section: Discussionsupporting
confidence: 93%
“…Combination of gramineae grasses with foliage or legume is one of the effective methods for the preparation of high-quality silage (Bureenok, Sisaath, Yuangklang, Vasupen, & Schonewille, 2016;Feng et al, 2012;Ge, Yang, & Liu, 2015;Muhammad, Baba, Mustapha, Ahmad, & Abdurrahman, 2008;Pan et al, 2014;Ridwan et al, 2015). The KG is a popular animal feed in tropics because it has high yield and good palatability.…”
Section: Discussionmentioning
confidence: 99%
“…Three-year average ADF contents of alfalfa genotypes indicated that Yesilova-1 (30.86%), Keciborlu-3 (30.50%), Cay-2 (30.98%), Huyuk-1 (31.09%), Bucak-3 (31.12%), K.Agac-3 (31.59%) and Yalvac-3 (31.67%) genotypes had lower ADF contents than the other alfalfa genotypes (between 34.36-30.91%). Alfalfa genotypes viz., Egirdir-2 (42.06%), Yalvac-3 (41.93%), Cay-1 (41.93%), Uluborlu-1 (41.87%), Suhut-1 (41.79%), Cay-2 (41.72 %), Keciborlu 3 (42.17%), Aksehir-2 (42.33 %), Sandikli-1 (42.41 %) Keciborlu 1 (42.45%), G.Dost-1 (42.54 %), Yesilova-1 (42.55 %) Bucak-3 (42.75 %), Huyuk-1 (42.90 %), Sandikli-3 (42.99 %), Aksehir-1 (43.07 %), Karamanli-1 (43.07 %), Yenisar-2 (43.14 %) and Cay-3 (43.15 %) alfalfa genotypes had lower NDF contents than the other alfalfa Jian et al, 2015;Kavut andAvcıoglu, 2015 Yuksek et al, 2016;Ahmad et al, 2016;Min, 2016;Malushi et al, 2017). Changes in harvest time with varieties and ecological factors have been shown to be effective on the ratio of ADF and NDF (Rimi et al, 2012), and genetic factors have also been implicated in alfalfa fiber content (Katic et al, 2008).…”
Section: Resultsmentioning
confidence: 98%
“…Alfalfa ( Medicago sativa L.) with high nutritive value is used primarily as major component of diets for high‐producing dairy cows (Schmidt et al., ) but also for horses, beef cattle, sheep, chickens, turkeys and other farm animals (Singh, ). Legumes such as alfalfa have greater buffering capacity than corn silage due to their high protein and mineral content, which means it takes more acid to lower the pH of legume silage (Jian et al., ). Therefore, it is necessary to use some additives to increase the supply of available carbohydrate substrates for the growth of lactic acid bacteria or to inhibit the activity of aerobic bacteria and decrease the loss of water soluble carbohydrate (WSC) in the early stage of ensilage (Shao et al., ).…”
Section: Introductionmentioning
confidence: 99%